2019
DOI: 10.1108/bepam-04-2018-0069
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing project data in BIM with descriptive analytics to improve project performance

Abstract: Purpose The purpose of this paper is to expand the benefits of building information modeling (BIM) to include data analytics to analyze construction project performance. BIM is a great tool which improves communication and information flow between construction project parties. This research aims to integrate different types of data within the BIM environment, then, to perform descriptive data analytics. Data analytics helps in identifying hidden patterns and detecting relationships between different attributes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In the design cycle, the designed artifacts are demonstrated, evaluated, and improved iteratively. Thereby, processes of LM, VE, BIM, and BDA, which are given in Figure 3, were also identified by compiling the studies of [12,[16][17][18]33,64,[68][69][70][71][72][73][74][75].…”
Section: Design Cycle (Desc)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the design cycle, the designed artifacts are demonstrated, evaluated, and improved iteratively. Thereby, processes of LM, VE, BIM, and BDA, which are given in Figure 3, were also identified by compiling the studies of [12,[16][17][18]33,64,[68][69][70][71][72][73][74][75].…”
Section: Design Cycle (Desc)mentioning
confidence: 99%
“…In the design cycle, the designed artifacts are demonstrated, evaluated, and improved iteratively. Thereby, processes of LM, VE, BIM, and BDA, which are given in Figure 3, were also identified by compiling the studies of [12,[16][17][18]33,64,[68][69][70][71][72][73][74][75]. After generating the tentative framework and its processes, expert interviews were used to evaluate the proposed maturity framework according to its processes, since Peffers et al [23] indicated that the evaluation of proposed artifacts could be performed based on expert evaluations, logical argument, technical experiment, subject-based experiment, action research, prototype, case study, and illustrative scenario.…”
Section: Design Cycle (Desc)mentioning
confidence: 99%
“…According to the needs of users, cloud providers can provide three types of public services, namely infrastructure, software and platform services. These delivery models are configured in different combinations [5]. If the cloud environment provided by the supplier can not correct the failure during the peak period of cloud users, it will cause immeasurable losses to users and reduce the overall confidence of cloud users [6].…”
Section: Big Data and Bim Technologymentioning
confidence: 99%
“…Some BIM related frameworks are based on the international assessment rating systems (Wong and Fan, 2013; Ansah et al , 2019; Jalaei et al , 2020), while others have created tools that are integrated into BIM design software to automate performance-based decision-making (Santos et al , 2020; Jaewook et al , 2020; Schlueter and Thesseling, 2009; El-Diraby et al , 2017; Edwards et al , 2019). Recent approaches have also employed big data analytics to improve performance (Marzouk and Enaba, 2019). Nonetheless, organisational aspects of BIM-enabled SBD have not been addressed sufficiently in the literature despite the fact that any resources for technology implementations should be split (Wilkinson, 2005; Shelbourn et al , 2007): 40% people, 40% process and 20% technology.…”
Section: Integration Of Sustainability Considerations Into Building Design Processesmentioning
confidence: 99%
“…al., 2020;Schlueter and Thesseling, 2009;El-Diraby, 2017;Edwards et al, 2019). Recent approaches have also employed big data analytics to improve performance (Marzouk and Enaba, 2019). Nonetheless, organisational aspects of BIM-enabled SBD have not been addressed sufficiently in the literature despite the fact that any resources for technology implementations should be split (Wilkinson, 2005;Shelbourn et al, 2007): 40 per cent people, 40 per cent process, and 20 per cent technology.…”
Section: Integration Of Sustainability Considerations Into Building Design Processesmentioning
confidence: 99%